Resolution based on the results of the conference: "RWD/ RWE – Research Tools of Real-World Clinical Practice Today and Tomorrow" - A. S. Kolbin (Реальная клиническая практика: данные и доказательства, 2021)
On September 16, 2021, the Association of Health Technology Assessment Professionals, the Association of Russian Clinical Pharmacologists, St. Petersburg Branch of ISPOR organized the II annual scientific and practical conference with international participation: "RWD/RWE – Research Tools of Real-World Clinical Practice Today and Tomorrow". The topic of the conference brought together leading Russian and world experts in the field of RWD/RWE.